2017
DOI: 10.20959/wjpps20179-10097
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of New Spectrophotometric Method for the Determination of Ticagrelor in Bulk and Pharmaceutical Formulation

Abstract: In this study a sensitive, simple and accurate spectrophotometric method is suggested for the determination of Ticagrelor in bulk and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This method can be conducted to fixed amount (0.4, 0.8) ml lotion pharmaceutical of 250 µg/ml to a series of volumetric flasks 25ml, increased volumes (0, 0.4, 0.8, 1.4, 1.8 ml) of the solution PYR of 250 µg/ml, and treated as in the calibration curve. The absorption of all solutions are measured at wavelength 550 nm, and the results are shown in the table (12) and fig (6). Results of standard additions is in good agreement with the direct method within the acceptable range of error, indicating that the method is satisfactory and free from interferences.…”
Section: -2 Standard Additions Methodmentioning
confidence: 74%
See 1 more Smart Citation
“…This method can be conducted to fixed amount (0.4, 0.8) ml lotion pharmaceutical of 250 µg/ml to a series of volumetric flasks 25ml, increased volumes (0, 0.4, 0.8, 1.4, 1.8 ml) of the solution PYR of 250 µg/ml, and treated as in the calibration curve. The absorption of all solutions are measured at wavelength 550 nm, and the results are shown in the table (12) and fig (6). Results of standard additions is in good agreement with the direct method within the acceptable range of error, indicating that the method is satisfactory and free from interferences.…”
Section: -2 Standard Additions Methodmentioning
confidence: 74%
“…It is found that the addition sequence (1) achieves a higher absorption of colored product, so it is adopted in subsequent experiments and the result are in table (5) shown. The temperature between (5 -60 °C) is effect on the absorption of the formed colored product, and the result shown in table (6).…”
Section: -5 Order Of Additionsmentioning
confidence: 97%